1976
DOI: 10.1139/v76-515
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen forming reactions of thermal electrons in hydrogen halides: kinetics and thermodynamics

Abstract: SURJIT S. NAGRA and DAVID ANTHONY ARMSTRONG. Can. J. Chem. 54, 3580 (1976). New competition kinetic studies of electron reactions in HCl and HBr in the 10Is to 1020 molecule cm-3 concentration region are reported and shown to support the findings of earlier investigations. The capture of thermal electrons by (HX): dimers is examined from a kinetic and thernrodynamic point of view. The (HX)2-'"intermediate previously proposed by several groups is considered to be involved in both systems. Differences in the mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1977
1977
2003
2003

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The slow electrons from the gas discharge attach to the growing clusters, which are "hot" due to the heat of condensation liberated in the clustering process. The existence of the (HC1)~ has been inferred earlier from reactions in v-irradiated high pressure HC1 [11]. As will be discussed elsewhere in more detail, Nmi .…”
Section: Discussionmentioning
confidence: 67%
“…The slow electrons from the gas discharge attach to the growing clusters, which are "hot" due to the heat of condensation liberated in the clustering process. The existence of the (HC1)~ has been inferred earlier from reactions in v-irradiated high pressure HC1 [11]. As will be discussed elsewhere in more detail, Nmi .…”
Section: Discussionmentioning
confidence: 67%
“…The magnitude of k,,, which determines the rate wheneveryN0-undergoes [21] (12) we find that 13% nitric oxide in HCl will captureelectrons at one tenth, one twentieth, and one fortieth the rate by HCI at concentrations of9.7 x 1018, 19.4 x 1018, and 38.9 x 1018 molecules cn1C3 respectively.…”
Section: Discussionmentioning
confidence: 76%
“…However, neither study gave a clear picture of the role of dimers or of the threshold energy for reaction (1). Evidence from radiation chemical studies conducted with gaseous HCl at 0.1 to 2 atmosphere pressure showed that thermal electrons could be captured, but the process was not an elementary DA as in reaction (1) 6, 22, 23. In that respect HCl differs from HBr, for which the threshold energy for reaction (1) is 0.0 eV and capture with thermal electrons is rapid 23–25.…”
Section: Introductionmentioning
confidence: 99%